Pengaruh Sosialisasi Perpajakan Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Badan Di Kawasan MM2100 - Jarkoni; Riris Hotmasari (LPPM STIE Bisnis Internasional Indonesia, 2021)
This research is motivated by the problem of the low compliance of taxpayers and tax revenues that have not reached the target. The purpose of this study is to examine the effect of tax socialization and tax sanctions on corporate taxpayer compliance in the MM2100 Region. The population in this study is corporate taxpayers in the MM2100 region totaling 190 companies. Calculation of the number of samples using a saturated sample that is all populations used as samples. The sample used in this study was 190 questionnaires distributed directly in the MM2100 area but only 92 questionnaires were returned. This research is a survey research with qualitative research type which is changed to quantitative. Data is processed with the IBM SPSS 25 program. The results showed that the taxation socialization variable and taxation sanction variables had a positive effect on corporate taxpayer compliance in the MM2100 region and taxation socialization and tax sanctions affected taxpayer compliance by 58.5%.